DEVELOPMENT OF VIRTUAL REALITY TECHNOLOGY: HOME TOUR FOR REAL ESTATE PURCHASE DECISION MAKING - Mohamad Kamil, Mohd Hafiz Faizal; Yahya, Najlaa; Zainal Abidin, Ira Syazwani; Norizan, Azir Rezha (Malaysian Journal of Computer Science, 2021)
Virtual reality (VR) is a technology; derived with various potential benefits for many aspects of rehabilitation assessment, treatment, and research. The emphasis of VR is computational rather than experiential. To preview Quill Residences houses, a buyer had to go to the showroom that was only located at two places in Kuala Lumpur. The showroom houses often lack depth and a sense of reality and take quite a bit of imagination to realize what the effect will look like in the real environment. There is a less interactive virtual reality walkthrough application from a local company for real estate marketing purposes. Therefore, this research aims to evaluate the effectiveness of interactive virtual reality walkthrough applications in home interior design for the real estate purchase decision. This research focuses on the interior design of Quill Residences and helps the real estate’s buyer to identify the home interior design criteria for the purchase decision. The current study has employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model representing a home tour immersive framework (HTIF) in creating practical resources to support VR application development. Results have shown that 90% of respondents believe that interactive virtual reality walkthrough application is effective in assisting the real estate’s purchase decision. Hence, this study will contribute to the effectiveness of interactive virtual reality walkthrough applications for real estate purchase decisions.